Strategi Fundraising LAZ Mandiri Amal Insani Surabaya dalam Menghimpun Dana Zakat - Roha Dewi Neta; Ufi Lailatuz Zakiyah; Fadhil Muhammad Akbar (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study analyzes the fundraising strategy implemented by LAZ Mandiri Amal Insani Surabaya in collecting zakat funds to support social empowerment programs. With a qualitative approach based on interviews and descriptive analysis, this study evaluates internal strategies, such as salary deductions from Bank Mandiri employees, and external strategies through zakat outlets, community collaboration, and the use of the my.berbagi.id digital platform. This strategy aims to increase community participation, build donor trust, and ensure targeted zakat distribution. The results of the study show that innovations such as the Customer Journey program and the use of digital technology contribute significantly to building donor trust. However, challenges such as low zakat literacy in the community and competition with other zakat institutions are obstacles that need to be overcome. This study emphasizes the importance of an effective and transparent fundraising strategy in expanding the reach of zakat collection and supporting the sustainability of social programs at LAZ Mandiri Amal Insani Surabaya. Keywords: Strategy, Fundraising, Zakat